Information System for Analyzing Disease Trends in the Region Cerenti Health UPTD - Dila Juniarti; Aprizal Aprizal; Sri Chairani (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
The Cerenti District Health Service is the implementing element of regional autonomy in the health sector which is located below and is accountable to the region through the regional secretary on the principles of regional autonomy and assistance duties. The performance of the system in managing data at the Cerenti Health UPTD, especially in reporting disease data, is not yet effective and efficient even though it uses a computer and stores data using Microsoft Word and Excel, because the creation and storage are separate, it still uses Microsoft Word and Excel, making it difficult to search for data. when needed again[1]. Management is designed to build a computerized system to make it easier for agencies to process data. The data processing created can manage disease reporting data more efficiently, effectively and can be controlled with data graphs [2]. With the final result of a computerized system, data processing will be more effective and efficient. This computerized system can store data properly so that it will avoid damage and loss of data [3]. With this computerized system, it will be easier to find data that has been stored for a long time [4]. With the existence of a computerized system regarding disease trends in the Cerenti Health UPTD area, it will provide a classification report on existing disease trends, based on data on patients who have contracted the disease.